Clinical Characteristics of COVID-19 Patients Infected by the Omicron Variant of SARS-CoV-2 - Zhang, Jianguo; Chen, Nan; Zhao, Daguo; Zhang, Jinhui; Hu, Zhenkui; Tao, Zhimin (Frontiers in Medicine, 2022)
Background Currently, as the omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surges amid the coronavirus disease 2019 (COVID-19) pandemic, its clinical characteristics with intrinsic severity and the protection from vaccination have been understudied. Methods We reported 169 COVID-19 patients that were infected with the omicron variant of SARS-CoV-2 and hospitalized in Suzhou, China, from February to March 2022, with their demographic information, medical/immunization history, clinical symptom, and hematological profile. At the same time, patients with none/partial (one-dose), full (two-dose) and three–dose vaccination were also compared to assess the vaccine effectiveness. Findings For the omicron COVID-19 patients included in this study, their median age was 33.0 [interquartile range (IQR): 24.0–45.5], 53.3% were male and the median duration from illness onset to hospitalization was 2 days. Hypertension, bronchitis, and diabetes were the leading comorbidities among patients. While the common clinical symptoms included cough, fever, expectoration, and fatigue, etc., asymptomatic patients took up a significant portion (46.7%). For hematological parameters, most values revealed the alleviated pathogenicity induced by the omicron variant infection. No critically ill or deceased patients due to COVID-19 infection were reported in this study. Interpretation Our results supported that the viremic effect of the omicron variant became milder than the previous circulating variants, while full vaccination or booster shot was greatly desired for an effective protection against clinical severity.